Gender Ideology on Marriage in Contemporary Vietnam - Hien Thi Nguyen; Lan Anh Hoang (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2019)
This paper examines how conservative gender ideology affects Vietnamese men’s and women’s belief in marriage with a focus on the importance of marriage to their personhoodand aspirations for ideal marital partners. Since marriage is a both legal and social recognition for the foundation and maintenance of families in a society, studying gender ideology on marriage helps to identify differences in men’s and women’s perspectives over marriage and how those views can reflect gender equality in the domestic sphere. The data on which this paper is based are part of a larger research project, namely “Understanding Gender and Marriage Ideology in Contemporary Vietnam” which was conducted in 2015. The results of the study indicate that marriage is still highly important to both Vietnamese men and women. Marriage is not only a social recognition regarding people’s individual achievements and gender identities but also a type of economic investment (in children) for their old age. In relation to marriage aspirations, Vietnamese people still base on genderrole ideology, which highlights men’s and women’s distinctive roles in familial life, to select their marital partners. The persistence of Confucianism in Vietnamese society is the main source for Vietnamese people to set up criteria for their ideal partners.